A study of the knowledge and problem solving ability of the family planning nurse in Mdantsane - Mathai, Mary (Department of Paediatrics and Child Health, 2018)
Women's control over their fertility is vital for both their health and that of their children. Although family planning methods are available at most health facilities in the country, the service does not enable many Black South African women to control their fertility successfully. This inadequacy of the present service is demonstrated, by a high rate of teenage pregnancy and abortion. Based on anecdotal reports, one of the barriers to effective use of contraceptive methods seemed to be the competence and abilities of the providers. This qualitative study was done in clinics in a peri-urban township to explore the knowledge and problem-solving abilities of the nurses providing family planning services. The aim was to use the information so gained to improve family planning services in the area by preparing a set of guidelines for the management of specific clinical problems and making recommendations to service organisers. The study tape-recorded 18 actual nurse-patient interactions to get an idea of the clinical problems faced by the nurses. A consensus panel was used to derive a set of "ideal" answers to the clinical scenarios the nurses faced in the consultations and the nurses' and panels' responses were compared. A focus group discussion with the nurses was then conducted and their opinions and reasons for the differences explored. The results revealed a general malaise affecting the services in this area. There were significant differences in the nurses and panels' handling of the problems especially in the areas of counselling and advice. In addition, the nurses were found to be inappropriate providers of family planning as their scope of practice prevented them from examining patients. They were also unable to rule out pregnancy because there were no pregnancy test kits available in the clinics. The focus group discussions indicated that many of the nurses knew how to handle the problems and what advice to give. They claimed that work and time pressures prevented them from doing this. They also alleged that patients were the problem and never told the truth. Poor communication skills and attitudes towards patients were other barriers identified. Nurses spoke to their patients like children and were often rude. In addition, nurses counselled patients infrequently on the use of methods and the side effects to be expected. Patients were offered a choice of method rarely and health education when given, focused on morality and did not mention issues like safe sex and HIV/ AIDS. The manual of guidelines will only address the problem solving of the nurses. The study therefore concludes by making recommendations to the Directorate of Maternal, Child and Women' s Health to carefully evaluate the use of enrolled nurses as providers with full consideration given to the quality of care that can be provided by them. The resources available and the practices related to supervision and in-service training also need to be reviewed and prioritised. A recommendation is also made to the Provincial Human Resources Directorate to develop policies for improving staff attitudes towards service users and disciplinary procedures for staff who are rude to service users. Recommendations are also made to supervisors to review the present training course and introduce the problem-solving approach and respect for patient autonomy into it. The supervision is also recommended to be facilitative and on-site and the providers must be involved in the solving of problems. The emphasis of the service must change from patient turnover to effective contraceptive use to enable women in this area to have any meaningful control over their fertility.